Self-Reported Health and Gender: The Role of Social Norms - Eve Caroli; Lexane Weber-Baghdiguian (Institute for the Study of Labor (IZA), 2016)
We investigate the role of social norms in accounting for differences in self-reported health as reported by men and women. Using the European Working Conditions Survey (EWCS, 2010), we first replicate the standard result that women report worse health than men, whatever the health outcome we consider – i.e. general self-assessed health but also more specific symptoms such as skin problems, backache, muscular pain in upper and lower limbs, headache and eyestrain, stomach ache, respiratory difficulties, depression and anxiety, fatigue and insomnia. We then proxy social norms by the gender structure of the workplace environment and study how the latter affects self-reported health for men and women separately. Our findings indicate that individuals in workplaces where women are a majority tend to report worse health than individuals employed in male-dominated work environments, be they men or women. These results are robust to controlling for a large array of working condition indicators, which allows us to rule out that the poorer health status reported by individuals working in female-dominated environments could be due to worse job quality. We interpret this evidence as suggesting that social norms associated with specific gender environments play an important role in explaining differences in health-reporting behaviours across gender, at least in the workplace.
Keywords: I12; I19; J16; 330; health; gender; social norms; job quality